Efforts to Improve Competency of Teacher MGMP Chemistry, Padang City Through Training For Development of Teaching Materials Based on Guided Discovery Learning - Yerimadesi Yerimadesi (Fakultas MIPA Universitas Negeri Padang, 2019)
This article is compiled based on the results of community service activities through the community partnership program of Padang State University in 2018 year. This activity aims to improve the competence of chemistry teachers in Padang City chemistry group through training based on guided discovery learning materials. The way to implement these activities can be done through training and workshops to 53 Padang chemistry group teachers. The instruments used were questionnaires for teacher and student responses. The product trial was carried out on 27 students of class X at Padang 1 Public High School in the 2018/2019 academic year. Data analysis was performed using percentage techniques and moment Cappa Cohen's. From the results of the questionnaire analysis of the chemistry teacher's response to the implementation and presentation of the material by the resource persons in succession, the average percentage percentage was 88% and 91% with the second category of aspects that being assessed very high. From the questionnaire analysis of teacher and student responses to learning using chemical modules based on guided discovery learning (GDL), the mean value of the kappa moment was 0.85 for the teacher's questionnaire responses with very high categories and 0.70 for the responses questionnaire of students with high categories. It was concluded that training in the preparation of teaching materials based on guided discovery learning could improve the competence of chemistry group teachers.